Climate Variability and Socioeconomic Vulnerability of Aquaculture Farmers in Malaysia - Rosita, Hamdan; Fatimah, Kari; Azmah, Othman (IACSIT Press, Singapore, 2011)
The aquaculture sector has undergone significant transformation in increasing food security for the nation as well as enhancing Malaysian Economic growth. This sector is put under the consideration of the Third National Agricultural Policy (1998-2010) in order to become the major area of concentration in fisheries production to improve the competitiveness of agriculture sector in Malaysia. At the national level, the development of aquaculture sector serves to resolve the insufficient fish supply as the main protein source of the household and reduces the social problems such as poverty, malnutrition and income inequality of the aquaculture farmers. Although the physical and financial drivers play their roles well in enhancing this sector, the climate variability provides major challenges in sustaining future outlook of aquaculture sector. Furthermore, the climate fluctuation raises the socio-economic vulnerability to aquaculture farmers due to the high production cost and production loss. The major concern of this study is to identify the association between climate variability and socio-economic vulnerability of the aquaculture farmers. Primary data was obtained from 120 aquaculture farmers in Sarawak, Malaysia. The findings revealed that there is significant association between climate variability and production loss especially when the water temperature changes and there is pandemic disease outbreaks. However, all factors have small effect on the aquaculture production loss. From the farmers’ view, other factor such as less dissolved oxygen, drought season, raining season and flood event were also factors that contributing to production loss. The results suggest that an effective and accurate adaptation strategy is needed to help aquaculture farmers cope with the climate variability impacts in their production. Keywords: climate variability, socio-economic vulnerability, aquaculture sector, production loss.